Organizational democracy and employee outcomes: The mediating role of organizational justice. Issue 3 (16th April 2019) - Ahmed, Kaleem; Adeel, Ahmad; Ali, Rizwan; Rehman, Ramiz Ur
Abstract: In the last two decades, scholars have proposed that implementing democratic practices and ideas in organizations results in significant improvements in employees' attitude and behavior. Using two widely advocated and debated dimensions of organizational democracy (empowerment and communication), the present study provides empirical evidence of this mentioned relationship between organizational democracy and employee outcomes (commitment, citizenship behavior, and turnover intentions) under mediating role of organizational justice. Based on the data of 262 employees working in fan manufacturing companies, structural equation modeling was employed to estimate the results. Results suggest that bringing democratization at workplace enhance employee commitment and citizenship behavior and reduce intentions to leave the organization. Furthermore, the study also supports organizational justice as a mediator, suggesting that the relationship between organizational democracy and employee outcomes becomes more strengthened once justice is introduced. The study provides empirical evidence to ideas and prepositions of many organizational democracy researchers working for decades.